1991
DOI: 10.1097/00000658-199111000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment for Surgical Peritonitis

Abstract: The charts of 480 patients with secondary bacterial peritonitis were reviewed. The antibiotics used were compared with the culture and sensitivity data obtained at surgery, and the outcomes of patients were evaluated. Patients treated with a single broad-spectrum antibiotic had a better outcome than patients treated with multiple drug treatment. Inadequate empiric antibiotic treatment was associated with poorer outcome than any other type of treatment. The outcome of this inadequate treatment group could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1
10

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(133 citation statements)
references
References 13 publications
10
112
1
10
Order By: Relevance
“…While Mosdell et al found appendicular perforation as most common cause for secondary peritonitis, also been confirmed by D Genne et al in their study. 2,11,16 The results of culture and sensitivity of the peritoneal fluid at laparotomy revealed that organisms isolated were E. coli (50%) followed by Klebsiella (24%), other organisms found were streptococci group D (12%), staphylococcus aureus (8%), Citrobacter (4%), and Candida in 10% patients and 16% patients revealed sterile culture. None of the 50 patients of peritonitis showed anaerobic isolation in present study due to noninclusion of suitable culture media for anaerobes and that seems to have become the major limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Mosdell et al found appendicular perforation as most common cause for secondary peritonitis, also been confirmed by D Genne et al in their study. 2,11,16 The results of culture and sensitivity of the peritoneal fluid at laparotomy revealed that organisms isolated were E. coli (50%) followed by Klebsiella (24%), other organisms found were streptococci group D (12%), staphylococcus aureus (8%), Citrobacter (4%), and Candida in 10% patients and 16% patients revealed sterile culture. None of the 50 patients of peritonitis showed anaerobic isolation in present study due to noninclusion of suitable culture media for anaerobes and that seems to have become the major limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies including Mosdell et al found that in appropriate initial antibiotic coverage was highly associated with persistent infection. 11 Hence, this study was done to study various organism found in cases of perforation peritonitis of difference sites of gastrointestinal tract and their sensitivity pattern, so as to form a recommendation for most effective empirical antibiotic regimen, so as to reduce morbidity and mortality. The study was done to identify the type of organism present in bowel perforation and their sensitivity pattern to different antibiotics.…”
mentioning
confidence: 99%
“…One epidemiological survey of patients with complicated intra-abdominal infections found an overall mortality rate of 6.0%, a postoperative abscess rate of 10.2%, and a re-operation rate of 12.5% [6]. Nonetheless, these data reflect the outcome of a heterogeneous group of patients at variable risks of treatment failure and death.…”
Section: Mazuski Imentioning
confidence: 99%
“…It is interesting that the source of the infection is not found to be an independent risk factor in these analyses. Thus, the lower mortality rate of patients with complicated appendicitis [6] may be related to their younger age and healthier condition as to the extent of peritoneal contamination, compared to patients with other types of intra-abdominal infections.…”
Section: Characterizing Patient Riskmentioning
confidence: 99%
See 1 more Smart Citation